Chemotactic sorting to cAMP in the multicellular stages of Dictyostelium development. - Traynor, D (1992)
Dictyostelium transformants that overproduce the extracellular form of cyclic nucleotide phosphodiesterase and so accumulate a reduced amount of cAMP are blocked in development after aggregation in the form of a tight mound, prior to formation of the apical tip. In such mounds, prespore cell differentiation is repressed, and the apical accumulation of prestalk cells is greatly retarded. When a source of cAMP is placed below the arrested mounds, prestalk cells that would normally migrate in an apical direction instead sort downwards to the substratum. Thus, by acting as the chemoattractant that draws prestalk cells to the apex, cAMP signaling directs the formation of a patterned structure.